Stepwise synthesis of Gly-Gly-His on gold surfaces modified with mixed self-assembled monolayers - Yang, Wenrong R (Langmuir : the ACS journal of surfaces and colloids, 2005)
Peptide-modified electrode surfaces have been shown to have excellent recognition properties for metal ions. An efficient method of screening a potential peptide for its selectivity for a given metal would involve the synthesis of the peptide directly on the electrode surface. This paper outlines a procedure in which the tripeptide Gly-Gly-His was synthesized one amino acid at a time on a gold surface modified with a self-assembled monolayer of the mixed alkanethiolates 3-mercaptopropionic acid (MPA) and 3-mercaptopropane (MP). Electrochemistry and high-resolution mass spectrometry were used to elucidate the structure of the adsorbed species and follow the synthesis. The amino acids can be attached only to MPA, but the presence of a diluting unreactive molecule of MP reduces steric crowding about the reaction center. The maximum coverage of synthesized tripeptide occurs at a ratio of MPA/MP of 1:1